English-Indonesian Translanguaging: Effects on EFL Students’ Vocabulary Acquisition and Concept Comprehension - Fransiska Orien Hieng; Carolina Pramesti Puja Lestari; Veronika Raymunda Nanga; Wendelinus Oscar Janggo (Jurnal Pendidikan dan Pembelajaran Indonesia (JPPI), 2025)
The purpose of this study is to examine the impact of English Indonesian translanguaging, the use of two languages simultaneously, on vocabulary acquisition and comprehension. The participants in this study were students from St. Maria Monte Carmelo Senior High School, Maumere, comprising 32 students from phases E1 and E2, who were selected through purposive sampling. The method employed was a descriptive qualitative approach, utilising instruments such as classroom observation, questionnaires, interviews, and vocabulary and concept understanding tests. The observation indicated that translanguaging was often used to explain the material and vocabulary, making it easier for students to learn the material. Then, the questionnaire data showed that the majority of students had a favourable view of translanguaging, indicating that students became more confident and comfortable while learning. In addition, the interviews revealed that students were not afraid to make mistakes due to the native language usage in the learning process. The test results showed that, on average, students demonstrated satisfactory vocabulary and concept understanding. This study suggests that translanguaging plays a crucial role in facilitating students' acquisition of new vocabulary and knowledge of concepts in the context of English as a foreign language.